Brahmanic Codes and Sanskrit Vocabulary in the Political Language of Islamic Preaching in Contemporary India - Parciack, Ronie (Religions of South Asia, 2015)
This article addresses the permeation of Brahmanic codes and Sanskrit vocabulary into popular Islamic preaching (da’wah), addressing the affinity of Indian Muslims to the contemporary Indian nation-state. Although the discourse of nationalism is customarily associated with secularization, and modern India is constitutionally defined as a secular democracy, the ideology of Hindutva (Hindu Nationhood) formed a unique discourse of nationalism that became dominant with the powerful rise of the Hindu Right as of the 1980s. Stated succinctly, Hindutva ideology establishes Indian nationalism on religious Hindu grounds, from which non-Hindus are structurally excluded. Nevertheless, Indian Muslim communities are actively seeking doctrinal paths to politically participate in the Indian polity and social space. This article addresses the contemporary field of popular Islamic preaching as a powerful arena for the rewriting of Islamic narratives and providing a re-signification of the Islamic presence in India via the presumably inaccessible Brahmanic route.